High-intensity training and salivary immunoglobulin A responses in professional top-level soccer players: Effect of training intensity - Owen, A. L.; Wong, D. P.; Dunlop, G.; Groussard, C.; Kebsi, W.; Dellal, A.; Morgans, R.; Zouhal, H (The Journal of Strength and Conditioning Research, 2016)
This study aimed (a) to test the hypothesis that salivary immunoglobulin A (s-IgA) would vary with training intensity sessions (low-intensity [LI] vs. high-intensity sessions [HI]) during a traditional training program divided into 4 training periods and (b) to identify key variables (e.g., GPS data, rating of perceived exertion [RPE], and training duration), which could affect s-IgA. Saliva samples of 10 elite professional soccer players were collected (a) before the investigation started to establish the baseline level and (b) before and after each 4 training sessions (LI vs. HI). Training intensity was monitored as internal (through heart rate responses and RPE) and external (through GPS) loads. High-intensity sessions were associated with higher external load (GPS) and with higher RPE. Baseline and pretraining s-IgA did not differ between the 4 training sessions both for HI and LI. Post-training s-IgA were not different (in absolute value and in percentage of change) between HI and LI sessions at the first 3 periods. However, at the fourth period, s-IgA concentration for HI session was significantly lower (p = 0.05) than the LI session. The percentage change between s-IgA post-training and s-IgA baseline concentrations differ significantly (p = 0.05) between HI and LI training sessions. Significant correlations between s-IgA and training intensity were also noted. High-intensity soccer training sessions might cause a significant decrease in s-IgA values during the postexercise window as compared with LI sessions. This study encourages coaches to monitor s-IgA in routine, particularly during HI training periods, to take precautions to avoid upper respiratory tract infection in highly trained soccer players.